Change in brain amyloid load in prodromal Alzheimer's disease patients after low-intensity ultrasound treatment - Kim, Jaeho; Jo, Sang Won; Park, Bo-yong; Park, Tae Young; Kim, Hyungmin; Kim, Min seung; Kang, Suk Yun; Cho, Soo-Jin; Kim, SangYun (Proceeding of NANS Annual Meeting 2024, 2024)
To investigate the efficacy and safety of lowintensity ultrasound (LIUS) using serial intravenous contrast-enhanced T1 mapping for the quantitative evaluation of glymphatic activity change and dynamic contrast-enhanced magnetic resonance imaging (DCE MRI) for the evaluation of blood-brain barrier(BBB) integrity in various brain regions in patient with Alzheimer's dementia (AD).